MOLECULAR PHYLOGENY OF INDONESIAN AGANAINE MOTHS (Lepidoptera: Noctuidae) BASED ON CO I GENE - Hari Sutrisno (Treubia, 2011)
Systematic of Aganaine moths has been long in dispute since they show both noctuids and arctiids morphological characteristics. Even the relationship among genera within Indonesian Aganaines is still unclear, and their phylogenetic relationships need to be reexamined since the morphological hypothesis proposed previously was not able to show the relationship among them. In order to clarify the phylogenetic relationship among five genera of Indonesian Aganaines, I used sequence of mitochondrial CO I gene (610-bp) to reconstruct their phylogenetic relationship using MP and NJ tree building methods. The results showed that the phylogenetic relationship proposed in this study contradicts the previous hypothesis. The monophyly of subfamily Aganainae has a strong bootstrap support at any tree building methods (88-95%). Neochera was divided into two clades and branched off first and then was followed by Euplocia, Peridrome, Agape, and Asota. The similarity between the previous hypothesis and this study is only on the sister-group relationship between Euplocia and Peridrome and the division of Neochera into two clades. The synapomorphy of Euplocia + Peridrome is a large androconial patch on the forewing upperside at the costal base. This study also showed that all internal nodes gained least supports. It indicates that the relationships among internal nodes proposed here were poorly supported due to the limited number of species and only a short fragment of one mitochondrial gene included in the analysis. Further studies are needed to be done by including more other species, other